Global Labour History: Perspectives from East to West, from North to South - Lampropoulou, Dimitra; Papastefanaki, Leda (Historein, 2020)
Historical reflection on the premises, risks and limitations of the global perspective in labour history has led to a new synthesis of theory and empirical research. The article introduces the conceptual framework and the main characteristics of a flourishing research area, that of global labour history. Finally, this introductory article presents the five articles of the special issue on “Global Labour History: Perspectives from East to West, from North to South”, and discusses how each of them is in dialogue with the topics addressed by global labour history.